Function determinants of TET proteins: the arrangements of sequence motifs with specific codes. (17th May 2019) - Liu, Dongyang; Li, Guangpeng; Zuo, Yongchun
Abstract: The ten-eleven translocation (TET) proteins play a crucial role in promoting locus-specific reversal of DNA methylation, a type of chromatin modification. Considerable evidences have demonstrated that the sequence motifs with specific codes are important to determine the functions of domains and active sites. Here, we surveyed major studies and reviews regarding the multiple functions of the TET proteins and established the patterns of the motif arrangements that determine the functions of TET proteins. First, we summarized the functional sequence basis of TET proteins and identified the new functional motifs based on the phylogenetic relationship. Next, we described the sequence characteristics of the functional motifs in detail and provided an overview of the relationship between the sequence motifs and the functions of TET proteins, including known functions and potential functions. Finally, we highlighted that sequence motifs with diverse post-translational modifications perform unique functions, and different selection pressures lead to different arrangements of sequence motifs, resulting in different paralogs and isoforms.